Seleção e desafio in vitro de bactérias probióticas isoladas do intestino do Tambaqui Colossoma macropomum Cuvier, 1818 - SILVA, Alexandre Vaz da (2023)
The present study aimed to isolate and select strains of bacteria with probiotic potential of the intestinal tract of Colossoma macropomum. Fifteen C. macropomum juveniles were reduced to isolate the bacteria, reduced for removal of the digestive tract, then the strains were subjected to in vitro assays, pH and other tests. The experimental design was randomized with different pH variations (4, 5, 6, 8 and 9) and a tube containing 5% (w / v) bile salts. For antagonism tests, four discs (Ø 0.8 cm) were removed and inoculated in TSA culture medium with pathogenic bacteria. Subsequently, as strains with the best results were identified. No total was isolated from 31 bacterial strains of C. macropomum juveniles, with 8 strains selected for in vitro assays. Strain T12A and T4A had a lower reduction in pH 6, 8 and 9 and, for the others, strain T12A decreased 9%. Regarding antagonism, such as T3AR, T4AR, T12A and T2AR strains, they stand out for pointing greater antagonistic action against Gram positive and Gram negative bacteria. Therefore, strain T12A was identified molecularly as Bacillus cereus, demonstrating probiótic potential for Colossoma macropomum (Tambaqui).